Initial ASIA impairment scale and its association with improvement in cervical spinal cord injury - Aman Singh; Somil Jaiswal; Anil Chandra; Amit Srivastava; Suresh Jaiswal; Awadhesh Yadav; B.K. Ojha; Chhitij Srivastava (Romanian Neurosurgery)
Background: Cervical spinal cord injuries (SCI) are a severe subset of trauma cases, with important impacts on functional abilities and quality of life. Effective management strategies are crucial for improving outcomes.